The identity of Inocellia sinensis Navás, 1936 (Raphidioptera: Inocelliidae) clarified - Shen, Rongrong; Aspöck, Horst; Aspöck, Ulrike; Liu, Xingyue (Zootaxa, 2021)
The identity of Inocellia sinensis Navás, 1936, is clarified based on the unexpected finding of the primary type of this species. The male of this species is re-described. Amurinocellia australis Liu, H. Aspöck, Yang & U. Aspöck, 2009 syn. nov. is treated as a junior synonym of I. sinensis, and I. aspoeckorum Yang, 1999 stat. rest. is restored as a valid species.